HUBUNGAN TINGKAT KEPARAHAN AKNE DENGAN KUALITAS HIDUP PADA MAHASISWA SENI TARI UNIVERSITAS TANJUNGPURA - Permata Iswari Sartika Dewi; Retno Mustikaningsih; Jojor Putrini Sinaga (JURNAL BORNEO AKCAYA, 2023)
Dance and Cosmetic makeup cannot be separated in a performance show, but some cosmetics can cause acne in dancers. Acne can reduce the quality of life for dancers. This study aims to determine the relationship between acne severity and dance students' quality of life. It is an observational analytic study that uses the cross-sectional method with a sample size of 28 students. The Questionnaire used to measure the quality of life is Acne Specific Quality of Life (Acne-QOL). A dermatologist examines the severity of acne. The determination of the severity of acne uses the American Academy of Dermatology. Based on Kendal's tau-b correlation analysis test results obtained 0,779 (P=0,00), it shows a strong relationship between the severity of acne and quality of life. The result is a relationship between the severity of acne and the quality of life of dance students. The more severe the severity of acne, the worse it will affect the sufferer's quality of life.